Polyimides based on aromatic diisocyanates containing pendent flexible alkoxy chains and aromatic dianhydrides: synthesis, characterization, and liquid-crystal alignment properties - Sarkar, Anjana; Halhalli, Mahadeo R.; Kulkarni, Arun D.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2009)
Four new aromatic diisocyanates containing pendent flexible alkoxy chains, namely, 5-butyloxy-1,3-phenylenediisocyanate, 5-octyloxy-1,3-phenylenediisocyanate, 5-dodecyloxy-1,3-phenylenediisocyanate, and 5-hexadecyloxy-1,3-phenylenediisocyanate, were synthesized by Curtius rearrangement of the corresponding 5-alkoxy-1,3-phenylene diacylazides. These diisocyanates were each polycondensed with three commercially available aromatic dianhydrides: 4,4'-oxydiphthalic anhydride, 3,3',4,4'-(hexafluoroisopropylidene) diphthalic anhydride, and 3,3',4,4'-benzophenonetetracarboxylic dianhydride-in benzonitrile in the presence of 1,4-dizabicyclo[2.2.2]octane as a catalyst to obtain a series of polyimides with inherent viscosities in the range 0.16-0.43 dL/g. Except for 3,3',4, 4'-benzophenonetetracarboxylic dianhydride based polyimides, all of the polyimides were found to be soluble in dichloromethane, m-cresol, 1-methyl-2-pyrrolidinone, tetra-chloroethane, and pyridine either at room temperature or on heating and could be cast into tough, flexible, transparent films from a solution in in-cresol or tetra chloroethane. X-ray diffractograms revealed that the polyimides with longer alkoxy chains had layered structures. The glass-transition temperature of the polyimides containing pendent flexible alkoxy chains were in the range 159-246 degrees C as measured by differential scanning calorimetry. The temperature for the 10% weight loss of the polyimides was in the range 410-460 degrees C in a nitrogen atmosphere, which indicated good thermal stability. A pretilt angle of 2.97 degrees was observed for the polyimide derived from 5-octyloxy-1,, 3-phenylenediisocyanate and 4,4'-oxydiphthalic anhydride. (c) 2009 Wiley Periodicals, Inc. J Appl Polym Sci 112: 461-472, 2009
Keywords: High performance polymers; polyimides; Thermal properties

Poly(amideimide)s containing pendant pentadecyl chains: synthesis and characterization - More, Arvind S.; Patil, Anandrao S.; Wadgaonkar, Prakash P. (Polymer Degradation and Stability, 2010)
A new aromatic diacylhydrazide monomer viz., 4-[4'-(hydrazinocarbonyl)phenoxy]-2- pentadecylbenzo-hydrazide was synthesized starting from cardanol, which in turn is obtainable from cashew nut shell liquid a renewable resource material. A series of new poly(amideimide)s containing flexibilizing ether linkages and pendant pentadecyl chains was synthesized from 4-[4'-(hydrazinocarbonyl)phenoxy]-2-pentade-cylbenzohydrazide and commercially available aromatic dianhydrides, viz., benzene-1,2,4,5-tetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, benzophenone-3,3',4,4'-tetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride and 4,4'-(hexafluoro isopropylidene)diphthalic anhydride by a two-step solution polycondensation in N,N-dimethylacetamide via the poly(hydrazide acid) intermediate. Inherent viscosities of poly(amideimide)s were in the range 0.60-0.64 dL/g in N,N-dimethylacetamide at 30 +/- 0.1 degrees C. Poly(amideimide)s could be solution cast into tough, transparent and flexible films from their N,N-dimethylacetamide solutions. The solubility of poly(amideimide)s was significantly improved by incorporation of pendant pentadecyl chains and were found to be soluble in N,N-dimethylacetamide, 1-methyl-2-pyrrolidinone, pyridine and m-cresol at room temperature or upon heating. Wide angle X-ray diffraction patterns of poly(amideimide)s revealed a broad halo at around 2 theta = similar to 19 degrees suggesting that polymers were amorphous in nature. In the small-angle region, diffuse to sharp reflections of a typically layered structure resulting from the packing of pentadecyl side chains were observed. The temperature at 10% weight loss (T(10)), determined by TGA in nitrogen atmosphere, of poly(amideimide)s was in the range of 388-410 degrees C indicating their good thermal stability. Glass transition temperatures of poly(amideimide)s were in the range 162-198 degrees C. It was observed that the plasticization effect of attached pentadecyl side chains induced the depression of T(g). (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Cardanol; Cashew nut shell liquid; Pentadecyl chains; Plasticization; Poly(amideimide)s; thermal stability

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Poly(ether ether ketone)s and poly(ether ether ketone ketone)s containing cardo decahydronaphthalene groups: synthesis and characterization - Honkhambe, Pandurang N.; Pasale, Sharad K.; Bhairamadgi, Nagendra S.; Kumbhar, Kishor P.; Salunkhe, Manikrao M.; Wadgaonkar, Prakash P. (Journal of Applied Polymer Science, 2011)
New poly(ether ether ketone)s and poly (ether ether ketone ketone) s were synthesized by polycondensation of each of the three bisphenols, viz., 4,4'-(octahydro-2(1H)-naphthylidene) bisphenol, 4,4'-(octa-hydro-2(1H)-naphthylidene) bis-3-methylphenol, and 4,4'(octahydro-2(1H)-naphthylidene) bis-3,5-dimethylphenol with 4,4'-difluorobenzophenone and 1,3-bis(4-fluorobenzoyl) benzene in a mixture of N,N-dimethylacetamide and toluene [1 : 1 (v/v)] in the presence of anhydrous potassium carbonate. Inherent viscosities of poly(ether ether ketone) s and poly (ether ether ketone ketone) s were in the range 0.32-0.80 dL/g and number-average molecular weights were in the range 16,100-55,900 g/mol. Poly(ether ether ketone) s and poly(ether ether ketone ketone) s were soluble in organic solvents such as dichloromethane, chloroform, tetrahydrofuran, meta-cresol, pyridine, and 1-methyl-2-pyrrolidinone at room temperature and could be cast into tough, transparent, and flexible films from their chloroform solutions. Wide angle x-ray diffraction measurements revealed the amorphous nature of poly(ether ether ketone) s and poly (ether ether ketone ketone) s. The glass transition temperature poly(ether ether ketone) s and poly(ether ether ketone ketone) s were in the range 185-251 degrees C. The temperature at 10% weight loss, determined from thermogravimetric analysis, of poly(ether ether ketone) s and poly(ether ether ketone ketone) s in nitrogen atmosphere was in the range 462-493 degrees C indicating their good thermal stability. (C) 2011 Wiley Periodicals, Inc. J Appl Polym Sci 122: 1607-1613, 2011
Keywords: bisphenol; cardo decahydronaphthalene; poly(ether ether ketone ketone)s; poly(ether ether ketone)s; Polycondensation; Thermal properties

Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization - Tawade, Bhausaheb V.; Salunke, Jagadish K.; Sane, Prakash S.; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2014)
A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50: 50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co) polyesters exhibited inherent viscosities in the range 0.70-1.21 dL g(-1) and number-average molecular weights in the range 16,000-48,200 (GPC, polystyrene standard). Polyesters were soluble in common organic solvents such as chloroform and dichloromethane and could be cast into films from chloroform solution. Polyesters exhibited T-10 values in the range 430-455 degrees C and Tg values were in the range 29-202 degrees C. Dynamic mechanical storage modulus and maximum on transition of tan delta curve decreased with increased content of HPPDP in copolyesters. Importantly, the large difference between Tg and T-10 values offers the possibility to process these polyesters in the melt.
Keywords: Aromatic polyesters; Cashew nut shell liquid; pentadecyl; Polycondensation; processability; Thermal properties

Pyrene based conjugated materials: synthesis, characterization and electroluminescent properties - Salunke, Jagadish K.; Sonar, Prashant; Wong, F. L.; Roy, V. A. L.; Lee, C. S.; Wadgaonkar, Prakash P. (Physical Chemistry Chemical Physics, 2014)
In this work, three novel pyrene cored small conjugated molecules, namely 1,3,6,8-tetrakis(6-(octyloxy)naphthalene-2-yl) pyrene (PY-1), 1,3,6,8-tetrakis((E)-2-(6-(n-octyloxy) naphthalene-2-yl) vinyl) pyrene (PY-2) and 1,3,6,8-tetrakis((6-(n-octyloxy) naphthalene-2-yl) ethynyl) pyrene (PY-3) have been synthesized by Suzuki, heck and Sonogashira organometallic coupling reactions, respectively. The effects of single, double and triple bonds on their optical, electrochemical, and thermal properties are studied in detail. These all materials are fluorescent and they have been used in organic light-emitting diodes (OLEDs) and their electroluminescent properties have been studied.

Polybenzimidazole-based polymeric ionic liquids (PILs): effects of `substitution asymmetry' on CO2 permeation properties - Shaligram, Sayali V.; Wadgaonkar, Prakash P.; Kharul, Ulhas K. (Journal of Membrane Science, 2015)
Polymeric Ionic Liquids (PILs) are being considered as promising membrane materials for CO2 separation. Present work aims at investigating effects substitution asymmetry on imidazole moiety of two structurally different polybenzimidazoles (PBI-BuI and PBI-HFA) on physical, gas sorption and transport properties of the resulting film forming PILs possessing symmetric substitution, while keeping one of the N-substituent as methyl group. PILs were obtained with high degree of substitution. The halide anion of these PILs was exchanged with BF4-, Tf-2(N) over bar and HF (B) over bar anions. Effects of substituents, cationic backbone and type of anions on gas permeation properties of PILs using pure gases (He, H-2, N-2 and CO2) were examined at 20 atm upstream pressure and correlated with their physical properties. Combination of typical ionic liquid character (effective towards enhancing CO2 sorption) and looser chain packing (ease in gas diffusion) offered improved CO2 permeation characteristics. As an outcome, some of the PILs exhibited higher CO2 permeation than that of hydrogen, typically known as `reverse selectivity'. These asymmetrically substituted PILs enhanced not only the gas permeability, but also selectivity than their symmetrically substituted counterparts. (C) 2015 Elsevier B.V. All rights reserved.

Phenothiazine and carbazole substituted pyrene based electroluminescent organic semiconductors for OLED devices - Salunke, Jagadish K.; Wong, F. L.; Feron, Krishna; Manzhos, Sergei; Lo, Ming Fai; Shinde, Durgaprasad; Patil, Abhijeet; Lee, C. S.; Roy, V. A. L.; Sonar, Prashant; Wadgaonkar, Prakash P. (Journal of Materials Chemistry C, 2016)
Due to their easy availability, low cost and opportunities for exploiting reactions of bromo substituents, 1,3,6,8-tetrabromopyrene has attracted major attention in the organic electronics community for designing and constructing novel classes of pyrene based organic semiconducting functional materials. In the present work, 1,3,6,8-tetrabromo pyrene was transformed into the corresponding tetrasubstituted carbazole and phenothiazine derivatives using the classical Suzuki coupling reaction. These newly synthesized materials with a carbazole substituent (PY-CA) and a phenothiazine substituent (PY-PH) were characterised thoroughly and were successfully used as an active light-emitting layer in organic light emitting diodes which resulted in blue and green emission with promising device performance. PY-CA exhibited the maximum brightness at around 2500 cd m(-2) and the power efficiency of 1.5 lm W-1 while that of PY-PH exhibited 2116 cd m(-2) and 0.45 lm W-1 respectively.

Problem solving and environmentally benign approach toward diversity oriented synthesis of novel 2-amino-3-phenyl (or Alkyl) sulfonyl-4H-chromenes at ambient temperature - Pandit, Kapil S.; Kupwade, Ravindra V.; Chavan, Pramod V.; Desai, Uday V.; Wadgaonkar, Prakash P.; Kodam, Kisan M. (ACS Sustainable Chemistry & Engineering, 2016)
A problem solving, environmentally benign, and diversity oriented protocol has been described for multi component synthesis of medicinally privileged 2-amino-3-phenyl (or methyl) sulfonyl-4H-chromenes by one-pot, three component condensation among aldehydes, phenyl (or methyl) sulphonyl acetonitrile, and alpha-naphthol, 3-dimethylamino phenol, 4-hydroxy-N-methyl-quinoline-2-one as well as 4-hydroxycarbazole, using diethylamine as an efficient organo catalyst. The catalyst employed is commercially available, inexpensive, and nontoxic. Ambient reaction conditions, very high yields, wide scope, and avoidance of conventional isolation as well as chromatographic purification have improved the practical utility of this protocol manifold.
Keywords: 2-Amino-3-methylsulfonyl-4H-chromenes; 2-Amino-3-phenylsulfonyl-4H-chromenes; diethylamine; green chemistry; Multicomponent synthesis; organocatalyst

Partially bio-based poly(amide imide)s by polycondensation of aromatic diacylhydrazides based on lignin-derived phenolic acids and aromatic dianhydrides: synthesis, characterization, and computational studies - Kuhire, Sachin S.; Sharma, Pragati; Chakrabarty, Suman; Wadgaonkar, Prakash P. (Journal of Polymer Science Part A-Polymer Chemistry, 2017)
Two new bio-based diacylhydrazide monomers, namely, 4,4-(propane-1,3-diylbis(oxy))bis(3-methoxybenzohydrazide) and 4,4-(propane-1,3-diylbis(oxy))bis(3,5-dimethoxybenzohydrazide) were synthesized starting from lignin-derived phenolic acids, namely, vanillic acid and syringic acid. A series of poly(amide imide)s was synthesized by polycondensation of these diacylhydrazide monomers with commercially available aromatic dianhydrides. Poly(amide imide)s showed inherent viscosity in the range 0.44-0.56 dLg(-1) and exhibited good solubility in organic solvents. Poly(amide imide)s could be cast into transparent, flexible, and tough films from their N,N-dimethylacetamide solutions. Poly(amide imide)s showed 10% weight loss in the temperature range 340-364 degrees C indicating their good thermal stability. Glass transition temperature (T-g) of poly(amide imides)s were measured by DSC and DMA which were in the range 201-223 degrees C and 214-248 degrees C, respectively. The T-g values of poly(amide imide)s were dependent on the number methoxy substituents on aromatic rings of diacylhydrazide monomers. Molecular dynamics simulation studies revealed that chain rigidity is the dominant factor for observed trends in T-g. (c) 2017 Wiley Periodicals, Inc.
Keywords: Biobased Polymers; Computational studies; Glass-transaction temperature; lignin; Monomers; Plant oils; Polyimide; Reneable resources; Renewable resources; Step-growth polymers; structure-property relations; Sustanaible Polymers; Thermal night; Thermosetting resins; Vanillin

Partially bio-based processable polyimides based on aromatic diamine derived from cardanol - Shingte, Rahul D.; Tawade, Bhausaheb V.; Wadgaonkar, Prakash P. (green Materials, 2017)
A partially bio-based aromatic diamine, namely, 1,1-bis(4-aminophenyl)-3-pentadecylcyclohexane (BAC15) was synthesized starting from cardanol. A series of polyimides were synthesized by one-step high-temperature solution polycondensation of BAC15 with aromatic dianhydrides. Copolyimides were also synthesised by polycondensation of various compositions of BAC15 and 4,4’-oxydianiline with 3,3’,4,4’-biphenyl tetracarboxylic dianhydride. Inherent viscosities and number average molecular weights of (co)polyimides were in the range 0.33-1.4 dL/g and 14700-31900 g/mol, respectively, indicating formation of reasonably high molecular weight polymers. Polyimides were soluble in common organic solvents such as chloroform, dichloromethane and tetrahydrofuran and could be cast into transparent, flexible and tough films from their solutions in chloroform. (Co)polyimides exhibited Tg in the range 161–254 °C. The lowering of Tg could be attributed to the presence of flexible pentadecyl chains which act as “packing disruptive” groups. The temperature at 10% weight loss (T10) of (co)polyimides was in the range 490–515 °C demonstrating their good thermal stability. The virtue of solubility and large gap between Tg and T10 offers (co)polyimides opportunities of both solution as well as melt processability. Copolyimides containing pendent pentadecyl chains exhibited pretilt angle in the range 2.51-2.75° indicating their potential application as alignment layer in liquid crystal display devices.

Phenothiazine-based D-A-π-A dyes for highly efficient dye sensitized solar cells: effect of internal acceptor and non-conjugated π-spacer on device performance - Nagane, Satyawan; Ichake, Amol; Agrawal, Ishita; Sadhanala, Aditya; Friend, Richard H.; Ogale, Satishchandra; Wadgaonkar, Prakash P. (ChemPlusChem, 2017)
Three new D-A-pi-A metal-free organic dyes based on phenothiazine as a donor (D) and non-conjugated pi-spacer were designed and synthesized. The incorporation of different 'internal acceptors' (electron traps) such as benzothiadiazole (BTD), benzotriazole (BTA), and pyridine were shown to allow systematic tuning of the energy levels and the photophysical properties. The AI-1 dye showed lower electronic disorder compared with the other two dyes. The efficiencies achieved with AI-1, AI-2, and AI-3 dyes were 8.5% (J(sc) = 15.42 mA cm(-2), V-oc = 0.78 V, FF = 68%), 7% (J(sc) = 12.8 mA cm(-2), V-oc = 0.78 V, FF = 68%) and 6.7% (J(sc) = 11.57 mA cm(-2), V-oc = 0.82 V, FF = 68.26 %), respectively. The incorporation of non-conjugated phenothiazine as a p-spacer in D-A-pi-A dyes showed remarkable enhancement in the photovoltaic performance of dye-sensitized solar cell (DSSC) devices. The sealed DSSC devices with iodide/tri-iodide (I-/I-3(-) @)based liquid electrolyte showed promising stability under ambient conditions.

Phenazine-containing poly(phenylenevinylene): a new polymer with impressive field emission properties - Chhatre, Shraddha; Ichake, Amol; Harpale, Kashmira; Patil, Sumati; Deshpande, Aparna; More, Mahendra; Wadgaonkar, Prakash P. (Journal of Polymer Research, 2018)
Phenazine-containing poly(phenylenevinylene) (P(PHN-PV)) was synthesized using Wittig-Horner polycondensation of the appropriately designed monomers viz. 5,10-dioctyl-5,10-dihydrophenazine-2,7-dicarbaldehyde and tetraethyl ((2,5-bis((2-ethylhexyl) oxy)-1,4 phenylene) bis(methylene)) bis(phosphonate). The design embraces the specific motivation of incorporating the nitrogen-containing heterocycle viz. .phenazine in poly(phenylenevinylene) backbone. P(PHN-PV) exhibited reversible redox properties. In the field emission measurements performed on the film of P(F'HN-PV), the turn-on field was observed to be 1.93 V/mu m for the current density of 10 mu A/cm(2). The maximum current density of similar to 4.87 mA/cm(2) was achieved at the applied field of 3.84 V/mu m. The emission current showed impressive stability for 6 h at a constant current of 1 mu A (current density of about 20 mu A/cm(2)). These results emphasize the role of phenazine heterocycle with lone pair of electrons on nitrogen in lowering the oxidation onset and in turn reduction of the turn-on voltage.
Keywords: field emission; Phenazine; Poly(phenylenevinylene)

Partially bio-based aromatic poly(ether sulfone)s bearing pendant furyl groups: synthesis, characterization and thermo-reversible cross-linking with a bismaleimide - Nagane, Samadhan S.; Kuhire, Sachin S.; Mane, Shivshankar R.; Wadgaonkar, Prakash P. (Polymer Chemistry, 2019)
A fully bio-based bisphenol bearing pendant furyl group, viz., 4,4'-(furan-2-ylmethylene) bis(2-methoxyphenol) (BPF) was synthesized by base-catalyzed condensation of furfural with guaiacol. New partially bio-based (co) poly(ether sulfone) s bearing pendant furyl groups were synthesized via aromatic nucleophilic substitution polycondensation of BPF and various mixtures of BPF and bisphenol-A with bis(4-fluorophenyl) sulfone in N, N-dimethylacetamide as a solvent. (Co) poly(ether sulfone) s showed inherent viscosities in the range 0.92-1.47 dL g(-1) and number average molecular weights ((M-n) over bar), obtained from GPC, were in the range 91 300-131 000 g mol(-1). (Co) poly(ether sulfone) s could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether sulfone)s showed 10% weight loss in the temperature range 431-481 degrees C and DSC showed T-g in the range 179-190 degrees C. Tensile strength, Young's modulus and elongation at break, obtained from tensile testing of (co) poly(ether sulfone) s containing pendant furyl groups, were in the range 76.7-83.8 MPa, 1.02-1.18 GPa and 21.4-89.7%, respectively. Most interestingly, pendant furyl groups in (co) poly(ether sulfone) s provide reactive sites for click modification and cross-linking via Diels-Alder reaction with maleimides and bismaleimides, respectively. Crosslinked (co) poly(ether sulfone) was prepared via Diels-Alder reaction of a representative (co) poly(ether sulfone) containing pendant furyl groups with 1,1'-(methylenedi-1,4-phenylene) bismaleimide (BMI) at 60 degrees C. The formation of cross-linked poly(ether sulfone) was demonstrated by gelation tests, solubility tests and DSC. The cross-linked copoly(ether sulfone) prepared using BMI showed enhanced tensile strength and Young's modulus compared to parent copoly(ether sulfone) and was recycled two times with retention of mechanical properties.

Partially bio-based furyl-functionalized organosoluble poly(ether ether ketone)s - Kuhire, Sachin S.; Talanikar, Aniket A.; Tawade, V, Bhausaheb; Nagane, Samadhan S.; Wadgaonkar, Prakash P. (Polymer International, 2021)
A new series of partially bio-based (co)poly(ether ether ketone)s bearing pendent furyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar proportions of 4,4 `-(furan-2-ylmethylene)bis(2-methoxyphenol) and bisphenol-A with 4,4 `-difluorobenzophenone. The chemical structures, compositions and random nature of (co)poly(ether ether ketone)s were confirmed by NMR spectroscopy. Inherent viscosities and number-average molecular weights of the (co)poly(ether ether ketone)s were in the range 0.74-2.90 dL g(-1) and 33 500-46 300 g mol(-1), respectively, indicating the formation of reasonably high molecular weight polymers. (Co)poly(ether ether ketone)s were readily soluble in common organic solvents and could be cast into tough, transparent and flexible films from chloroform solutions. (Co)poly(ether ether ketone)s exhibited 10% weight loss and glass transition temperatures in the range 429-464 and 152-156 degrees C, respectively. A representative copoly(ether ether ketone) was crosslinked with 1,1 `-(methylenedi-1,4-phenylene)bismaleimide via Diels-Alder reaction to form a crosslinked polymer which showed improved mechanical properties and was recycled twice without significant loss of mechanical properties. Diels-Alder/retro Diels-Alder reaction was demonstrated by studies of sol-gel transformation, solubility tests, DSC and stress-strain measurements. (c) 2020 Society of Chemical Industry
Keywords: aromatic poly(ether ether ketone)s; bio-based; crosslinking; Diels-Alder reaction; pendent furyl groups

Partially bio-based triarylamine-containing polyimides: synthesis, characterization and evaluation in non-volatile memory device applications - Chatterjee, Deepshikha; Jadhav, Uday A.; Javaregowda, Bharathkumar H.; Dongale, Tukaram D.; Patil, Pramod S.; Wadgaonkar, Prakash P. (European Polymer Journal, 2021)
A new triarylamine-containing diamine, viz. 4, 4'-diamino-4 `' pentadecyltriphenylamine was synthesised starting from cashew nut shell liquid (CNSL) - a non-edible by-product of cashew processing industry. Three new partially bio-based triarylamine-containing polyimides were synthesised by one-step high temperature solution poly-condensation of 4, 4'-diamino-4 `' pentadecyltriphenylamine with aromatic dianhydrides, namely, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexa-fluoroisopropylidene) diphthalic anhydride (6-FDA). Polyimides were determined to be of reasonably high molecular weights as inherent viscosity and number average molecular weights (M-n, Polystyrene standard) values were in the range 0.54-0.60 dL g(-1) and 26,800-43,500 g mol(-1), respectively. Polyimides exhibited excellent solubility in common organic solvents and film-forming nature along with reasonably good thermal properties as indicated by temperature for 10% weight loss (T-10) and glass transition temperatures (T-g) which were in the range 418-447 and 165-225 degrees C, respectively. The optical and electrochemical band-gap values were in the range of 1.95-1.98 eV and 1.671-1.745 eV, respectively. Among triarylamine-containing polyimide devices, BPDA-based device showed acceptable current-voltage and non-volatile memory properties such as the endurance of 500 cycles and 1000 s of retention time. The conduction mechanism developed in the memory devices was also explored and was found to follow Ohmic and Schottky conduction mechanisms.
Keywords: Bio-based polyimides; CNSL; Memory device; pentadecyl; Triarylamine

Pendant propargyloxy-functionalized aromatic (co)polycarbonates: synthesis, thermal crosslinking and chemical modification - Nagane, Samadhan S.; Maher, Deepak M.; Verma, Savita; Talanikar, Aniket A.; Wadgaonkar, Prakash P. (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2022)
A bisphenol monomer bearing pendant propargyloxy group viz, 1, 1-bis (4-hydoxyphenyl)-1-(4 `-propargyloxyphenyl) ethane (BPP) was synthesized starting from commercially available 1, 1, 1-tris (4-hydroxyphenyl) ethane (THPE) by mono O-propargylation reaction using propargyl bromide. A new series of pendant propargyloxy-functionalized aromatic (co)polycarbonates was synthesized by low-temperature solution polycondensation of BPP or different molar ratios of BPP and bisphenol-A with triphosgene in dichloromethane in the presence of triethylamine. The formation of reasonably high molecular weight (co)polycarbonates was confirmed by inherent viscosity (0.52-0.83 dL/g) and gel permeation chromatography (M-n 37,000-69,800 g/mol, polystyrene standards) measurements. C-13 NMR spectral studies supported formation of random copolycarbonates in copolymerization of BPP and BPA with triphosgene. The 10% weight loss temperature (T-10) values of (co)polycarbonates, determined by thermogravimetric analysis under nitrogen atmosphere, were in the range 427-438 degrees C indicating their good thermal stability. The glass transition temperature (T-g) values of (co)polycarbonates were observed in the range 147-152 degrees C. The crosslinking ability of (co)polycarbonates involving pendant propargyloxy groups leading to formation of networked structure was evaluated via non-isothermal curing studies by DSC. As a proof-of-concept, the post-modification of a representative polycarbonate bearing pendant propargyloxy groups with 1-octane thiol as a model compound via thiol-yne click reaction was briefly studied.
Keywords: Aromatic polycarbonate; Chemical modification; propargyloxy groups; thermal crosslinking; thiol-yne click reaction

Post-polymerization modifiable aromatic (co)poly(ether sulfone)s possessing pendant norbornenyl groups based upon a new bisphenol - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (European Polymer Journal, 2022)
A new bisphenol possessing pendant norbornenyl group viz., 4, 4 `-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) was synthesized by a single-step base-catalyzed condensation reaction of 5-norbor-nene-2-carboxaldehyde with guaiacol. NMR spectral data indicated formation of BPA-NB comprising of isomeric components. A series of (co)poly(ether sulfone)s possessing pendant norbornenyl groups was synthesized by nucleophilic aromatic substitution polycondensation of varying molar ratio of BPA-NB and bisphenol-A (BPA) with bis(4-fluorophenyl) sulfone. Inherent viscosity values and number average molecular weights of (co)poly (ether sulfone)s were in the range 0.67-1.01 dL/g and 75,400-1,16,300 g/mol, respectively indicating the formation of reasonably high molecular weight polymers. Tough, transparent, and flexible films could be cast from chloroform solutions of these (co)poly(ether sulfone)s. (Co)poly(ether sulfone)s were characterized using FT-IR, H-1 NMR and C-13 NMR spectroscopy, XRD, TGA and DSC analysis. The formation of random copoly(ether sulfone)s was demonstrated by( 13)C NMR analysis. The incorporation of BPA-NB into (co)poly(ether sulfone)s resulted into improvement in Tg values. BPA-NB-based (co)poly(ether sulfone)s offered possibilities for post -modifications involving either methoxyl or norbornenyl groups. A representative copoly(ether sulfone) (PSU-NB-2) possessing pendant norbornenyl groups was chemically modified via thiol-ene reaction with three representative thiol compounds, namely, 1-dodecanethiol, 2-furanmethanethiol and 2-mercaptoethanol to yield corresponding post-modified polymers in a quantitative manner. Additionally, it was demonstrated that copoly (ether sulfone) possessing pendant norbornenyl groups could be used to form insoluble cross-linked gel in the presence of a multifunctional thiol cross-linker.
Keywords: (Co)poly(ether sulfone)s; bisphenol; Cross -linking; Pendant norbornenyl groups; Thiol-ene reaction